Radiation sensitivity of Aspergillus niger of low-energy X-rays and Caesium-137 gamma rays - Nguyễn, Thị Thùy Linh (Elsevier Ltd, 2024)
The radiation sensitivities of Aspergillus niger in several energy X-rays and gamma rays were investigated. Experiment and simulation were conducted to evaluate the X-ray energy spectra and depth dose distributions. The result showed that the microbicidal effectiveness of Aspergillus niger could depend only on the dose regardless of photon energy. It should be noted that the depth dose of low-energy X-rays, including characteristic X-rays of tungsten (LIIIab-ray and Lα-ray of 8.4 keV and 10.2 keV, respectively) is variable even at 1 mm.